Passive Resistance. Notes for a more complete understanding of the resistance practices of the rural population during the Franco dictatorship - Ana Cabana Iglesia (Amnis)
The dictatorship established by General Franco in Spain after the Civil War (1936-1939) sought to de-mobilize the entire population and, particularly, to achieve the full passivity of the rural population. As a consequence, historiography has mechanically characterized the passive attitudes of the peasantry as evidence of its « collaboration » and/or « consent » with the Franco regime. Lack of action is difficult to interpret and often ratifies the identification of indifference with support for the regime, but this should not be taken as an axiom. The object of our research is to re-visit the passivity that was activated at times by the rural population as a display of resistance that can be interpreted as a form of boycotting state policies and initiatives.